Spiritual care for prevention of psychological disorders in critically ill patients: study protocol of a feasibility randomised controlled pilot trial - Jan Bakker; Paula Repetto; Carolina Ruiz; Verónica Rojas; Patricia Olivares; Leyla Alegria (BMJ Open)
Introduction A significant number of critically ill patients who survive their illness will experience new sequelae or a worsening of their baseline health status following their discharge from the hospital. These consequences may be physical, cognitive and/or psychological and have been labelled postintensive care syndrome (PICS). Prior research has demonstrated that spiritual care aligned with a specific creed during hospitalisation in the intensive care unit (ICU), as part of a comprehensive care plan, may be an effective strategy for preventing psychological sequelae in surviving critically ill patients. However, there is a gap in clinical literature regarding the effectiveness of generalist spiritual care in preventing psychological sequelae associated with PICS. This pilot study aims to explore the feasibility of implementing a generalist spiritual care strategy in the ICU and to evaluate its preliminary effectiveness in preventing anxiety and depression symptoms and post-traumatic stress disorder in critically ill patients.Methods and analysis This is a single-site, feasibility randomised controlled pilot trial of a generalist spiritual care intervention compared with the current standard of care. A total of 30 adults who are critically ill and have undergone invasive mechanical ventilation for a minimum of 72 hours without alterations in consciousness will be randomly assigned to either the spiritual care group or the usual care group at a ratio of 1:1. The primary outcome will be the feasibility and acceptability of the spiritual care strategy in critically ill patients. Secondary aims include evaluating the differences in anxiety and depression symptoms and post-traumatic stress disorder between the spiritual care group and the usual care control group at 3 months after ICU discharge. Subjects will be followed up until 3 months post-ICU discharge.Ethics and dissemination The Ethics Committee for Medical Sciences of Pontificia Universidad Católica de Chile (#220111005) and the Ethics Committee of Servicio de Salud Metropolitano Sur Oriente approved the study. Pontificia Universidad Católica de Chile funded the study (project number 105699/DPCC2021). The findings will be widely disseminated through peer-reviewed publications, academic conferences, local community-based presentations, partner organisations and the Chilean Intensive Care Society.Trial registration number NCT06048783.